Structural and functional properties of neodymium-doped hydroxyapatite nanoparticles for biomedical applications - K.Sai Manogna; K. Kusuma; G.Rajasekhara Reddy; B.Deva Prasad Raju; N.John Sushma (Biotechnology Reports)
Neodymium (Nd³⁺) doped hydroxyapatite nanoparticles (Han: Nd³⁺ NPs) were synthesized and systematically characterized to evaluate their structural and functional properties for biomedical applications. X-ray diffraction (XRD) confirmed the crystalline phase retention post-doping, while x-ray photoelectron spectroscopy (XPS) revealed the successful incorporation of Nd³⁺ ions. The doping altered the optical and electronic properties, potentially enhancing bioactivity and imaging capabilities. Preliminary cytotoxicity assessments on MCF7 and 4T1 breast cancer cell lines indicated dose-dependent effects, with IC50 values of 36.13 µg/mL and 64.38 µg/mL, respectively. The study concludes that Han: Nd³⁺ NPs offer promise as multifunctional platforms for cytotoxic response and structural stability, with potential for future application in imaging and targeted breast cancer therapy.